One-year predictors of PTSD symptoms, anxiety, and depression in SARS-CoV-2 survivors: psychological flexibility and major life events as main predictive factors - Carvalho, Sérgio A.; Pinto, Helena; Carreiras, Diogo; Palmeira, Lara; Pereira, Marco; Trindade, Inês A. (Frontiers in Psychology, 2024)
Introduction The COVID-19 pandemic held considerable health-related outcomes worldwide, including mental health challenges, with elevated risk of psychiatric sequelae. Methods This study aimed to test the longitudinal (1 year) predictive role of psychosocial factors on post-traumatic stress disorder (PTSD), anxiety, and depressive symptoms in SARS-CoV-2 survivors (N = 209 at T1; N = 61; attrition rate 70.83%), through Pearson’s correlation analyses and longitudinal multiple regression analyses. Participants (age M = 35.4, SD = 10.1) completed online self-report questionnaires of psychosocial variables, PTSD, anxiety, and depression. Results Depression and anxiety symptoms were increased, and 42% of survivors presented clinically meaningful PTSD symptoms. PTSD symptoms were longitudinally predicted by having children (β = 0.32, p < 0.01), number of recent major life events (β = 0.34, p < 0.01), and psychological flexibility (β = −0.36, p < 0.01). Number of major life events (β = 0.29, p < 0.05) and psychological flexibility (β = −0.29, p < 0.05) predicted anxiety. Number of recent major life events (β = 0.32, p < 0.01) was the sole predictor of depressive symptoms. Discussion Psychosocial variables contribute to the long-term harmful effects of the COVID-19 pandemic on psychopathological symptoms. These results suggest that, during the pandemic, mental health was impacted by both socio-contextual factors and individual self-regulatory skills, namely the ability to respond flexibily to contextual cues and guide behavior according to the direct experience. Specifically, results point out the importance of societal incentives to reduce parental burden and socioeconomic losses, as well as to promote adaptive psychological skills such as psychological flexibility.